Mewujudkan Pembelajaran Kejuruan yang Nyaman: Implementasi Kaidah Ergonomi dalam Praktek Pengelasan di SMK Negeri 1 Purworejo - Yuyun Estriyanto; Komarudin Komarudin; Towip Towip; Taufik Wisnu Saputra; Indah Widiastuti (FKIP Universitas Sebelas Maret, 2024)
Various welding positions and extended durations of welding practice sessions can contribute to Musculoskeletal Disorders (MSDs) complaints among Vocational High School (SMK) students. MSDs encompass conditions that manifest symptoms affecting muscles, nerves, tendons, ligaments, joints, cartilage, and the spinal cord. The implementation of an ergonomic welding table may assist welding operators in working on projects for prolonged periods with a reduced risk of MSDs complaints. This article reports on the community service activities conducted by the Vocational and Mechanical Engineering Education research group at Universitas Sebelas Maret in developing and implementing an ergonomic welding table at SMK Negeri 1 Purworejo. Ergonomic parameters used for reference include the Nordic Body Map (NBM), Rapid Entire Body Assessment (REBA), and Rapid Under Limbs Assessment (RULA). The pre and post experiment analysis indicates a decrease in NBM, REBA, and RULA scores following the implementation of the ergonomic welding table, suggesting the potential for minimizing MSDs complaints.